CHRONIC LOW BACK PAIN IN INDIVIDUALS WITH LOWER-LIMB AMPUTATION - Kušljugić, Ademir (Bosn J Basic Med Sci, 2006)
Low back pain (LBP) is a common condition in individuals which experienced psychology and physical trauma. LBP is usually found in persons with lower-limb amputation (LLA), as the most common sign of somatisation or inappropriately made prostheses. Our goal was to investigate cases of chronic pain syndrome in persons with LLA and to determine factors, which influence their functional inability due to LBP. Pain after LLA has been studied. 37 persons, including 26 war veterans (70,2 %) and 11 (29,8 %) civilians with LLA due to an illness, were examined. All participants gave their informed consent and filled Oswestry index of disability due to chronic LBP, divided into 10 sections with 6 questions each, with marks in the range 0-5. The average age of 37 analyzed participants with LLA was 46,2+-10,92 years. 30 participants (81,1 %) were married, 4 (10,8 %) were single and 3 (8,1 %) were widows. 27 (73,0 %) participants had below the knee amputation, 5 (13,5 %) had above the knee amputation and 5 (13,5 %) had foot amputation. 33 (89,6 %) participants experienced chronic LBP in the last 2-10 years and 4 (10,8 %) did not have pains. According to Oswestry index for chronic pain higher level of social functionality was found in civilian amputees than in war veterans (p<0,05). Married civilian amputees have higher level of disability during seating (p<0,01), sleeping (p<0,01) and traveling (p<0,05). Higher level of social disorder among civilian amputees is due to the fact that they belong to older group of participants which usually have social integration at the lower degree. More serious problems during seating, traveling and sleeping among this group are probably due to co morbidity. Chronic LBP was found among 89,6 % of the participants. Higher level of social disorder, problems during seating, traveling and sleeping were identified in the civilian amputees and the married participants.